INTERSECTION OF SURROGACY AND WOMEN’S REPRODUCTIVE HEALTH UNDER THE SURROGACY (REGULATION) ACT, 2021 - Kachore, Mamta Vitthalrao; Khobragade, Dr. Pravina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Reproductive health entails a wide range of concerns that are associated with human reproductive system, fertility, contraception as well as maternal health. In India reproductive health includes a number of activities and option, among them surrogacy seem to have provided an effective solution to couple facing barrenness. The Surrogacy (Regulation) Act, 2021 is a major landmark in the domain on surrogacy law and ethics in India. The Act, being enacted for proper legal recognition of and protection to surrogate mothers and intended parents who seek surrogacy services, prescribe strict parameters and conditions for the contract of surrogacy. In continuation of the theme of surrogacy and women reproductive rights within the new legal regime this paper aims to examine the effect of this new legal regime on all parties of concern. This research aims at assessing how these provisions advanced in the following areas: Legal exploitation, ethics aspects, surrogate mothers and intended parents. The current paper aims at discussing the Surrogacy (Regulation) Act, 2021 in association with reproductive health and surrogacy procedures in India. It examines the role of the Act in relation to some of the previous legal and ethical issues concerning and the considerations provoked by its implementation. Through the provisions of the Act and its implications, this study extends knowledge of the means through which legal changes can improve reproductive health practices and address surrogacy ethicality.